Credit Rating Agencies and Iceland: the effect of rating announcements on government bonds - Guðbjörg Erla Ársælsdóttir 1993- (2016)
The financial markets in Iceland have endured immense volatility in the last 10 years. The 2008 financial crisis caused massive havoc but the Icelandic economy has been adjusting since, more than most people thought was possible. Credit rating agencies offer their opinion on the creditworthiness of an issuer of debt. These agencies have had to keep up with the changes in the Icelandic economy during this period, downgrading the sovereign several times. Only recently, in 2015, was the rating of the Republic of Iceland upgraded. The purpose of this research is to analyze the daily price changes of long term Icelandic government bonds after a rating agency issues an announcement regarding the creditworthiness of the government, and explore whether and if so, to what extent, the market reacts to those announcements in the period of 2006-2016. The study examines a thirteen day period before and after an announcement is made by Standard & Poor’s, Moody’s and Fitch. Prior studies have found that downgrades have a negative effect on bond prices and upgrades have a positive effect. Studies show that downgrades matter more to market participants than upgrades. The results of this thesis revealed that only a few rating announcements had a significant effect on the prices of government bonds. The announcements that affected the price changes of the government bonds mostly occurred in 2008, a fragile time in the Icelandic financial environment, so other factors not included in the analysis may have affected the price changes. Further research is needed to fully see the determinants of the prices of government bonds, as well as the role that credit rating announcements play in the formation of prices of Icelandic government bonds.